GREEN AND EFFICIENT SYNTHESIS AND CHARACTERIZATION OF AMINO CHROMENE DERIVATIVES WITH ADD ALKYL TAIL - Madasamy Kumar , Veerappan Jeyachandran (International Journal of Modern Agriculture, 2020)
The reaction between substituted 4-hydroxy benzaldehyde, active methlyene compounds and/or resorcinol yield amino chromene derivatives. Structures of these compounds were established upon the basis of IR, 1HNMR, 13CNMR, and MASS data.